1999
DOI: 10.1063/1.478870
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the hydrogen exchange reaction at 2.20 eV collision energy: Comparison of experimental and theoretical differential cross sections

Abstract: The HϩD 2 (vϭ0,jϭ0)→HD(vЈ, jЈ)ϩD isotopic variant of the hydrogen atom exchange reaction has been studied in a crossed molecular beam experiment at a collision energy of 2.20 eV. Kinetic energy spectra of the nascent D atoms were obtained by using the Rydberg atom time-of-flight technique. The extensive set of spectra collected has permitted the derivation of rovibrationally state-resolved differential cross sections in the center-of-mass frame for most of the internal states of the HD product molecules, allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 42 publications
5
56
0
Order By: Relevance
“…Indeed, various quantum results show that forward scattering is exclusively due to partial waves with high total angular momentum J, which corresponds to high impact parameters. 4,9,11 Although the classical dynamics is unable to reproduce quantum effects such as interferences and tunneling and, thus, cannot reproduce certain experimental results accurately, QCT results are nonetheless in surprisingly good agreement with experimental and QM cross sections for this reaction, 2,8,14 which shows that the nuclear dynamics is predominately classical. In particular, we have recently demonstrated that the QCT method can give valuable insight into the motions of the nuclei during a reactive encounter and, thus, elucidate reaction mechanisms.…”
Section: 10supporting
confidence: 60%
“…Indeed, various quantum results show that forward scattering is exclusively due to partial waves with high total angular momentum J, which corresponds to high impact parameters. 4,9,11 Although the classical dynamics is unable to reproduce quantum effects such as interferences and tunneling and, thus, cannot reproduce certain experimental results accurately, QCT results are nonetheless in surprisingly good agreement with experimental and QM cross sections for this reaction, 2,8,14 which shows that the nuclear dynamics is predominately classical. In particular, we have recently demonstrated that the QCT method can give valuable insight into the motions of the nuclei during a reactive encounter and, thus, elucidate reaction mechanisms.…”
Section: 10supporting
confidence: 60%
“…Later work by Kuppermann and co-workers [5], [55]- [58] using multivalued basis functions approach to include the GP, considered more general effects where the unsymmetrized wave function may encircle the CI. Their calculations predicted strong GP effects in the differential cross sections (DCS), but these predictions were neither reproduced by later calculations that omitted the GP [9,11,24], nor by experiments [8,10]. Detailed experimental results agreed quantitatively well with theoretical predictions ignoring the GP boundary condition.…”
supporting
confidence: 71%
“…Calculations by Kuppermann and co-workers in the early 90s predicted significant differences in experimental observables between calculations ignoring and including the GP effect [47,48]. Experimental measurements however were a very good fit to theory that did not take the GP into account [2,[7][8][9]12,49]. Following earlier work by Kendrick [50], Althorpe and co-workers [33,37,38,51,52] succeeded in proving definitively that the GP has no effect on the ICS and only a minor effect on the DCS at E coll < ∼ 4 eV.…”
Section: Discussionmentioning
confidence: 80%
“…A different reaction mechanism has been discovered for highly internally excited HD(ν , j ) products of the H + D 2 → HD(ν , j ) + D reaction, wherein rotationally excited molecules become more backward scattered than the rotationally cold ones [9,10]. In addition, highly internally excited HD(ν , j ) products, particularly the HD(ν = 4, j ) manifold, exhibit a more isotropic angular distribution [9][10][11][12]. The deuterium atom Rydberg tagging technique was employed in the study of an H + HD → H 2 (ν , j ) + D hydrogen exchange variant [13,14], where the forward peak has been attributed to the well-known time-delayed mechanism observed in the H + D 2 → HD(ν = 2, 3, j = 0) + D reaction [8,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%